Pengaruh Pasca Pandemi Covid-19 Terhadap Kegiatan Ekstrakurikuler - Yasin, Muhammad (Universitas Palangka Raya, 2023)
The impact of Covid-19 on school extracurricular activities is enormous. When covid-19 cases were still rampant, school extracurricular activities were automatically hampered and not carried out properly as usual. However, after the completion of the Covid-19 pandemic, the impacts are still very much felt. Like still trying to adapt to the current environment. During the current recovery period, the school's extracurricular activities are also still trying to adapt as well as the existing students they have to adapt again to extracurricular activities directly or face-to-face after about 2-3 years of not carrying out these extracurricular activities. Adjustments to schedules, locations, and extracurricular coaches are some examples of what schools are currently doing, including MAN Kota Palangkaraya. Currently, Palangkaraya City MAN is trying to revive their existing extracurricular activities.